(untitled) (Journal of Hama University, 2024)
This research was carried out within the framework of the joint cooperation between the General Authority for Scientific Agricultural Research and Tishreen University in the period between 2021-2022, and it aimed to study the effect of extraction treatments, including the effect of the type of solvent and. Temperatures (60-40-25 °C) on the percentage of the resulting colloidal yield, and then choose the treatment with the highest yield and study its sensory, physicochemical and functional properties. The results of the statistical analysis showed that treatment B (isopropanol - temperature 40°C) had the highest yield with high significant differences with other treatments and its value reached up to and this treatment was chosen to study the aforementioned characteristics. By conducting preliminary confirmatory tests of the colloidal extract, it was found that the studied powder is a starch-free carbohydrate mucilage product. The resulting colloidal powder was acceptable in terms of smell and taste. The results of chemical composition estimation showed that the resulting powder contained a high percentage of ash and protein, which is 12.92 ± 0.71 and 10.62 ± 0.32. As for the physicochemical properties, the solution prepared at a concentration of 1% was neutral in terms of pH, and the relative viscosity, refractive index and swelling index were good and they are on respectively 1.230 ± 0.03 CPs 1.336 ± 0.05 and 3.67 ± 0.02 g water / g dry powder, and with regard to the functional indicators, the values of water holding capacity, oil holding capacity and emulsifying ability were good, respectively, 2.21 g water / g powder 1.98 g oil / g powder 38 % , and it was found that the resulting powder solution has a good ability to form foam . The results of this study indicate that the colloidal powder of malva leaves can be considered a biopolymer applicable in food and pharmaceutical industries.